RESEARCH ON LOADS ON UAV STRUCTURE BASED ON SOLIDWORKS MOTION SIMULATION AND MEMS ACCELEROMETER DATA - SVACHII, OLEH; BOIKO, JULIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Unmanned Aerial Vehicles (UAVs) play a crucial role in modern applications, spanning a wide range of industries such as defense, agriculture, medicine, scientific research, and manufacturing. The performance and flight stability of UAVs are largely ensured through the use of microelectromechanical system (MEMS) sensors, particularly gyroscopes and accelerometers. In most cases, MEMS gyroscopes serve as the primary tool for flight stabilization, while accelerometers act as auxiliary components. However, MEMS accelerometers possess significant potential for motion analysis of UAVs, particularly in determining the forces acting on the drone during flight. This study investigates the dynamic characteristics of UAV motion and the influence of forces through the development of a 3D quadcopter model and simulations conducted in SolidWorks Motion. The basic simulations took into account the mass properties of the structure and gravitational force acting on the quadcopter. Several motion scenarios were implemented, including straight-line flight, acceleration, and directional change maneuvers. The primary objective of this work is to identify the forces occurring during UAV flight using data collected from the onboard accelerometer, by evaluating changes in acceleration measured by the MEMS accelerometer. Understanding these forces provides deeper insight into the real-world operating conditions of UAVs, enabling improvements in structural design, system functionality, and motion control algorithms. The results of the study demonstrate that MEMS accelerometers can be used not only as auxiliary devices but also as analytical tools for assessing motion dynamics and external forces acting on the UAV. The results of the study demonstrate that MEMS accelerometers can be used not only as auxiliary de but also as analytical tools for assessing motion dynamics and external forces acting on the UAV.
Keywords: loading forces; MEMS; SolidWorks Motion simulation; Unmanned Aerial Vehicle (UAV)